PENGARUH INTEGRITAS, KOMPETENSI AUDITOR, DAN RISIKO AUDIT TERHADAP KUALITAS AUDIT DENGAN SKEPTISME PROFESIONAL AUDITOR SEBAGAI VARIABEL MODERASI - Hamidah, Hamidah; Idzni, Nurul; Hakimah, Sayyidah; Sonia, Sonia; Muhsin, Muhsin (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2024)
This study aims to analyze integrity, auditor competence, and audit risk on audit quality and analyze professional skepticism in moderating integrity, auditor competence, and audit risk on audit quality. This research was conducted by auditors at the Representative of the West Kalimantan Financial and Development Supervisory Agency (BPKP). The data was obtained by filling out a questionnaire distributed to BPKP via Google form. The total number of questionnaires received was 30 respondents. The analysis method used in this study is Structural Equation Modeling (SEM) with the use of WarpPLS version 8.0 application. This study found that integrity, auditor competence, and risk can have a positive effect on audit quality. Professional skepticism can moderate auditor integrity and competence on audit quality, but professional skepticism cannot moderate audit risk on audit quality.